2006
DOI: 10.1097/01.aids.0000232232.41877.2a
|View full text |Cite
|
Sign up to set email alerts
|

Impact of occult hepatitis B virus infection in HIV patients naive for antiretroviral therapy

Abstract: The study suggests that HBV occult infection, relatively frequent in anti-HIV-positive patients, is associated with hepatic flares.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
80
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(97 citation statements)
references
References 34 publications
11
80
3
3
Order By: Relevance
“…OBI has also been described as a serological condition characterized by the presence of hepatitis B core antigen (anti-HBc) in the absence of HBsAg and anti-HBs (isolated anti-HBc) [7,[11][12][13][14][15] . OBI may be observed in the window period of acute HBV infection [16] in blood donors and in recipients of blood and blood products [9,17,18] , in patients with HCV chronic infection [7,19] , in cryptogenic chronic hepatitis, in patients under pharmacological suppression of the immune system [20,21] and in those with immunodepression due to HIV infection; it has also been associated to the development of hepatocellular carcinoma [22][23][24][25][26][27][28][29][30] . It has been shown that the hepatitis B virus maintains its pro-oncogenic properties in OBI [31] and that its presence in patients with chronic hepatitis C is associated with a higher risk of disease progression and HCC development [32][33][34][35][36] and with a reduced response to alfa interferon treatment [37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…OBI has also been described as a serological condition characterized by the presence of hepatitis B core antigen (anti-HBc) in the absence of HBsAg and anti-HBs (isolated anti-HBc) [7,[11][12][13][14][15] . OBI may be observed in the window period of acute HBV infection [16] in blood donors and in recipients of blood and blood products [9,17,18] , in patients with HCV chronic infection [7,19] , in cryptogenic chronic hepatitis, in patients under pharmacological suppression of the immune system [20,21] and in those with immunodepression due to HIV infection; it has also been associated to the development of hepatocellular carcinoma [22][23][24][25][26][27][28][29][30] . It has been shown that the hepatitis B virus maintains its pro-oncogenic properties in OBI [31] and that its presence in patients with chronic hepatitis C is associated with a higher risk of disease progression and HCC development [32][33][34][35][36] and with a reduced response to alfa interferon treatment [37][38][39] .…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of abnormal ALT values was also higher among HCV-infected occult HBV-infected subjects than HCVuninfected (54.4% versus 30.1%; p<0.005). Filippini et al [Filippini et al, 2006] found that hepatic flares (defined as an increase in ALT >3 times prior value) occurred more commonly among HIV patients with occult HBV infection than in those without occult HBV infection (64.7% versus 24.6%, p<0.005) over a median 18 months follow-up after the initiation of antiretroviral therapy. Our results might differ because we controlled for relevant confounders (i.e., alcohol use, HAART, and chronic HCV).…”
Section: Discussionmentioning
confidence: 99%
“…All HBsAg-positive refugees and undocumented immigrants were referred to the nearest tertiary care unit of infectious diseases for further investigation, monitoring, and possible treatment. These units have cooperated for over 15 years in several clinical investigations, using the same clinical approach and the same laboratory methods (13,27,28). The cultural mediators assisted the HBsAg-positive subjects both at the first-level and third-level care facilities units.…”
Section: Study Populationmentioning
confidence: 99%
“…HBV-DNA serum levels were determined by a realtime PCR with a detection limit of 20 copies/mL as previously described (27). HBV genotypes were determined in HBV-DNA-positive serum samples (31).…”
Section: Hbv-dna Determination By Pcrmentioning
confidence: 99%
See 1 more Smart Citation